Investigating the thermal comfort effects of daylighting as a passive design strategy at McDonald's Alor Setar buildings in Kedah / Nurul Fatihah Asyiqin Sazali and Jamaludin Muhamad - Sazali, Nurul Fatihah Asyiqin; Muhamad, Jamaludin (2023)
This research investigates the thermal comfort perception of passive daylighting strategies implemented in a McDonald's restaurant building in Alor Setar, Kedah. The study explores the relationship between daylighting and users' thermal perception to enhance the dining experience through optimal thermal conditions. Previous studies have suggested that daylighting does not directly impact users' thermal comfort in restaurant buildings but affects the environment's ambient temperature. Therefore, this study utilizes controlled experimental observations to understand the interplay between all relevant factors better. Data collection involved measuring daylight lux levels, ambient and room temperatures, three participants' skin temperatures, and their subjective responses after 30 minutes of daylight exposure. The results indicate that exposure to daylight influences the ambient temperature of the surrounding environment. Higher lux levels result in increased temperatures due to heat gain. The findings reveal that users perceive warmer sensations when exposed to higher temperatures under high daylight illuminance levels (lux levels), compared to medium and low illuminance levels, and vice versa. This study contributes to a deeper understanding of the variable factors that impact users' thermal comfort perception in indoor environments, particularly in restaurant settings where ensuring user comfort is crucial for successful design outcomes.